METHODS OF GROWING MEDICINAL PLANTS IN INVITRO CONDITIONS - Shokirova Gavkharkhan Nazirgulomovna; Shirmatova daughter of Madinabonu Odiljon (Web of Journals Publishing, 2024)
Methods for growing medicinal plants in vitro make it possible to reproduce biological processes in laboratory conditions and control the physiological state of plants. These methods play an important role in changing the genetics of plants, quickly obtaining quality crops and protect ix from harmful diseases. Using in vitro technologies, it is possible to accelerate the propagation of medicinal plants, improve various external characteristics and growth rate.
Keywords: Medicinal plants, Plant cloning, Biotechnology. Plant regeneration, Genetic modification, Plant crops, biological diversification, Plant genetic resources.